Governance of Homestay in Cibuntu Tourism Village, Kuningan Regency, West Java, Indonesia - Savitri Hendradewi; Anis Darsiah; Irfal; Filma Festivalia; Anita Swantari (Program Studi Manajemen Divisi Kamar, 2025)
This study aims to analyze homestay governance in Cibuntu Tourism Village, Kuningan Regency, West Java, by highlighting interactions between stakeholders, community adaptation strategies, and opportunities for developing sustainable governance models. Homestays were chosen as the focus of the study because they are a crucial node in community-based tourism (CBT) practices and a key pillar of sustainable village tourism. The research method employed a qualitative approach with a case study design. Informants were selected through purposive sampling involving homestay owners, Pokdarwis (Tourism Group) administrators, village officials, and private sector partners. Data were obtained through in-depth interviews, participant observation, and documentation studies, and were then analyzed thematically. The results showed that families still manage most homestays without uniform service standards, although the family atmosphere is a key attraction. Pokdarwis plays a crucial role, but community participation remains limited. In conclusion, homestay governance needs to be strengthened through the principles of good governance, expanded participation, and the integration of sustainable tourism as recommendations for the development of other tourism villages in Indonesia.